Subsurface dynamics of buoyant microplastics subject to algal biofouling. Issue 9 (26th June 2021) - Kreczak, Hannah; Willmott, Andrew J.; Baggaley, Andrew W.
Abstract: Mathematical modeling offers an avenue to predict distributions of microplastics in the ocean. With this goal in mind this study presents a simple analytic model describing the deterministic dynamics of long‐time vertical motion of buoyant microplastics that have succumbed to biofouling in a quiescent ocean. The model couples equations governing vertical particle position and algal population dynamics and is formulated in a nondimensional frame work to determine the minimum number of system parameters. We present results which give a comprehensive understanding of the system's key dynamics when varying four parameters. Previous studies have shown that biofouling causes microplastic particles to oscillate below the ocean's surface; however, for the first time we are able to identify the fundamental processes that govern the microplastic trajectories. The model demonstrates that plastic particle properties are the biggest factor in determining the period and characteristics of the oscillation profile, while the algal population dynamics determine the maximum depth reached. As the fouled particles cross the pycnocline their long‐term behavior is to become trapped within a subsurface layer, bounded by the depth of the euphotic zone and the seasonal pycnocline. The smallest particles are extremely sensitive to algal cell attachment and growth suggesting they are always submerged at depths surrounding the base of the euphotic zone or could become trapped in large algal colonies. In general, the results suggest that a higher concentration of biofouled microplastic is expected to be found subsurface, trapped close to the euphotic zone depth rather than at the ocean's surface.